2008
DOI: 10.1007/s10560-008-0120-6
|View full text |Cite
|
Sign up to set email alerts
|

Institutionalization, Romanian Adoptions and Executive Functioning

Abstract: The impact of a traumatic environment during early childhood is linked to short-term and long-term difficulties in adoptees. This study, utilizing a nonrandom, cross-sectional analysis of 123 children adopted from Romania, focused on executive cognitive functioning. One-third of the sample had not been institutionalized while the other two-thirds had been institutionalized for varying lengths of time from 1 month to more than 3 years, resulting in a ''natural experiment'' that allowed us to compare these two g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…In addition, the 51% response rate is lower than the 66% of one of the largest international adoption follow‐ups (Gunnar et al, 2007) but higher than the 28–36% of the largest follow‐up of children adopted from Romania (Groza, Ryan, & Thomas, 2008). Responders and non‐responders did not differ significantly in the child’s mean age at adoption (15.61 vs. 16.65 months; t (988) = 1.07, ns ).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In addition, the 51% response rate is lower than the 66% of one of the largest international adoption follow‐ups (Gunnar et al, 2007) but higher than the 28–36% of the largest follow‐up of children adopted from Romania (Groza, Ryan, & Thomas, 2008). Responders and non‐responders did not differ significantly in the child’s mean age at adoption (15.61 vs. 16.65 months; t (988) = 1.07, ns ).…”
Section: Discussionmentioning
confidence: 91%
“…PI children adopted at older ages after more prolonged institutional deprivation often have higher rates of cognitive, behavioral, and social problems (MacLean, 2003). Likewise, age at adoption effects have been found for children’s performance on EF tasks (Colvert et al, 2008) and parent and teacher ratings of child EF (Groza et al, 2008; Jacobs et al, 2010), although some results have been non‐significant or inconsistent (Bos et al, 2009; Pollak et al, 2010), perhaps because the PI groups in these studies were restricted to children adopted after 9–12 months of age.…”
Section: Age At Adoptionmentioning
confidence: 88%
See 1 more Smart Citation
“…One study found no differences compared with a normative sample in adopted preschool children aged 2-5 y (14), whereas another found that 11% of children aged 4-5 y had EF problems in the clinical range according to parent ratings (34). The third study did not include a comparison group (35); thus, the authors were only able to conclude that parents of PI children reported more EF problems than teachers did. Observational laboratory studies are needed to clarify whether EF performance is lower in this group and can be detected in this age range.…”
Section: Ef In Postinstitutionalized Childrenmentioning
confidence: 97%
“…In the few studies of parent- or teacher-rated EF in everyday contexts, PI children had greater EF difficulties than children reared in their biological families (Bruce, Tarullo, & Gunnar, 2009; Groza, Ryan, & Thomas, 2008; Jacobs, Miller, & Tirella, 2010; Merz & McCall, 2011). PI children’s EF task performance was significantly associated with parent-rated EF (Bruce et al, 2009) and with parent- and teacher-rated attention problems (Colvert et al, 2008; Stevens et al, 2008).…”
Section: Executive Functioning In Post-institutionalized Childrenmentioning
confidence: 99%